Mariticide in Milan between 1990 and 2017: A criminological and medico-legal analysis. (December 2019) - Merzagora, Isabella; Battistini, Alessio; Caruso, Palmina; Mottale, Nicole; Pleuteri, Lorenza; Travaini, Guido
Most murder victims in a romantic relationship are women but sometimes they will kill their husbands or partners (mariticide). This paper focuses on these rarer cases using a sample taken from the autopsy reports of the Department of Legal Medicine of the University of Milan whose territory includes the municipality of Milan and part of the province of Milan and Monza – approximately four million inhabitants.